The relationships between personality and the system of values in the case of the national team female field hockey players - Wojtowicz, A.; Basiaga-Pasternak, J.; Kosiba, G.; Bogacz-Walancik, A. (Studies in Sport Humanities, 2015)
The aim of the study was to determine the predictors of female sports success by examining the relations between personality and the system of values in female field hockey players. The research was conducted among the members of Polish National Field Hockey Team. The average age was 21,42 (SD = 4,49). The study suggested that within the examined group the most important terminal values were Happiness and Family Security, and the least important - Salvation and A World of Beauty. Among instrumental values the most important were Love, Ambition, Responsibility and Honesty. The least important values in the group were Imagination and Obedience. The personality type was related to the system of values. The study suggested that among the examined sportswomen the dimension Neuroticism was connected with the importance of Freedom, A Comfortable Life and Wisdom. Openness was related to the importance of A World of Beauty, Self-Control, A Sense of Accomplishment, and Family Security. Extraversion was connected with the decrease in Obedience, A World at Peace and Equality values, but with the increase of the importance of Independence. Conscientiousness was connected with the increase of the importance of Responsibility and Self-Respect, but with the decrease of the importance of Helpfulness, Forgiveness and Imagination. Agreeableness was related to the increase in Forgiveness.